2015
DOI: 10.1089/jmf.2014.0171
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Polyphenol-Rich Chokeberry Juice Consumption on Blood Pressure Level and Lipid Status in Hypertensive Subjects

Abstract: Epidemiological studies have shown a positive association between intake of foods rich in antioxidants and lower incidence of cardiovascular disease development. Polyphenols are considered the most abundant and important dietary antioxidants. The aim of this study was to evaluate effects of polyphenol-rich chokeberry juice consumption on 24-h ambulatory monitored blood pressure (BP) level in subjects with no pharmacologically treated high normal BP or grade I hypertension. Twenty-three subjects (12 men and 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
88
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(96 citation statements)
references
References 36 publications
5
88
3
Order By: Relevance
“…The beverage size in our pilot study was chosen in accordance with the amount of aronia juice (100 ml) to be consumed in mentioned clinical trial testing platelet function. This was rationalised by the amount of total polyphenols, as active compounds of interest and in accordance with amounts that have been shown as effective in our previous research (Kardum et al 2014a(Kardum et al , 2014b(Kardum et al , 2015.…”
Section: Testing Of the Final Placebo Formulation: Pilot Studysupporting
confidence: 79%
See 2 more Smart Citations
“…The beverage size in our pilot study was chosen in accordance with the amount of aronia juice (100 ml) to be consumed in mentioned clinical trial testing platelet function. This was rationalised by the amount of total polyphenols, as active compounds of interest and in accordance with amounts that have been shown as effective in our previous research (Kardum et al 2014a(Kardum et al , 2014b(Kardum et al , 2015.…”
Section: Testing Of the Final Placebo Formulation: Pilot Studysupporting
confidence: 79%
“…In accordance with the duration of intervention phases in this clinical trial, we have chosen 4-week intervention period for our pilot study. In addition, our previous research indicated that 4-week interventions with Aronia juice could express beneficial effects on blood pressure, blood lipids, including fatty acid status, and pro-oxidant/antioxidant status (Kardum et al 2014a(Kardum et al , 2015. The beverage size in our pilot study was chosen in accordance with the amount of aronia juice (100 ml) to be consumed in mentioned clinical trial testing platelet function.…”
Section: Testing Of the Final Placebo Formulation: Pilot Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to previous studies from our lab, which found that purified berry (blueberry and strawberry) anthocyanins supplemented in the drinking water, but not whole berries, decreased serum cholesterol and triglyceride level [26]. In addition, hypertensive adults who were fed chokeberry juice daily for four weeks showed significant reductions in triglyceride levels, total and LDL cholesterol and systolic and diastolic blood pressure [15]. Similar effects were observed in patients with metabolic syndrome who were supplemented with chokeberry juice for two months [16].…”
Section: Discussioncontrasting
confidence: 99%
“…A recent study by Qin and Anderson [11] demonstrated that chokeberry extract prevented weight gain and decreased risk factors associated with insulin resistance in rats fed a fructose-rich diet through modulation of multiple pathways associated with insulin signaling, adipogenesis and inflammation [11]. In addition, supplementation with chokeberry juice reduced blood pressure and improved lipid status in both hypertensive individuals [15] and individuals with metabolic syndrome [16].…”
Section: Introductionmentioning
confidence: 99%